PEMETAAN KEJADIAN BENCANA ALAM TANAH LONGSOR KABUPATEN MAJALENGKA MENGGUNAKAN SIG (SISTEM INFORMASI GEOGRAFIS) - Susanti, Deffy; Taupik Qurohman, Rifki (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2021)
Majalengka Regency is one of the districts with very high rainfall considering the recent natural disasters in the Majalengka Regency area such as landslides that have occurred in several districts. And also seen from the characteristics of the area of Majalengka Regency, a landslide risk area mapping was carried out using the Geographical Information System (GIS) which aims to provide information on locations that are at risk of landslides. Quantum GIS is an open source and cross-platform Geographical Information System (GIS) application that can be run on a number of operating systems. The minimal use of open source software that is legal, as well as being used as a material for assessing the capabilities of the open source software in completing spatial data processing and analysis using the SDLC Waterfall method. when the disaster happened.